Institutional Ethos of Less Selective Massive Private Universities in Chile: Organizational Identities in a Competitive and Marketized University System - Maria Luísa Quaresma; Cristóbal Villalobos; Andrés Rojas-Murphy; Francisco Molina-Salas (MDPI AG, 2024)
This article aims to reflect on the institutional ethos of three Chilean, less selective massive private universities, analyzing their organizational identities, discourses, and practices and discussing how the dynamics of the competitive and marketized Chilean educational system influence this ethos. Through a qualitative design, which includes semi-structured interviews with key university staff members and direct observations in formal and informal instances, this article concludes that the ethos of these institutions is structured around four main axes: pluralism and student diversity; the pursuit of excellence as a competitive horizon; the construction of merit as a personal, family, and institutional effort; and education for employability, underpinned by professional ethics and social commitment. Furthermore, we find evidence that the logic of the university market shapes these private universities' ethos transversally.